Potential additives for small-scale wood chip combustion – Laboratory-scale estimation of the possible inorganic particulate matter reduction potential. (15th October 2019) - Gollmer, Christian; Höfer, Isabel; Harms, Daniel; Kaltschmitt, Martin
Highlights: Addition of additives increases the ash content of wood chips. Selected additives are able to increase the potassium retention in wood chip ash. Kaolinite, anorthite and aluminum hydroxide show high potential for PM mitigation. Abstract: The objective of this study is to analyze the influence of five different additives (i.e., kaolinite, anorthite, calcium silicate, titanium dioxide, and aluminum hydroxide) in the lab-scale to estimate their suitability for (inorganic) particulate matter (PM) emission reduction of beech wood chips during small-scale combustion. Therefore, ashes at five different temperatures (i.e., 550 °C, 700 °C, 900 °C, 1000 °C, and 1100 °C) are produced for each biomass-additive-mixture and analyzed with respect to their potassium content and potassium recovery rate being typically the most important PM component. Additionally, the crystalline fractions of the ash samples are analyzed by X-ray diffraction to allow for conclusions on the potassium retention ability of the used additives. Finally, thermogravimetric analyses are conducted for the obtained 550 °C ashes in addition to the ash analysis. By evaluating and assessing the analytical results for the different biomass-additive-samples, the additives kaolinite, anorthite, and aluminum hydroxide are identified as the most promising ones with respect to the potentially achievable inorganic PM reduction during the small-scale wood chip combustion.